THE APPLICATION OF ACTIVITY BASED COSTING ARE: ELIMINATION IN THE CALCULATION OF COST OF PRODUCTION PT SEMEN TONASA (PERSERO), PANGKEP REGENCY - Menne, Firman (Journal of Humanity, 2013)
Economic conditions should be viewed as the catalyst for developing the ability to intelligently manage resources so that the people of Indonesia can be out of the condition. Effective management and efficiency is reflected in good planning and good planning requires good information. In order to plan well the utilization of company resources to fold the duplicate spiders, company management requires system information revealed by clearly and precisely the facts relating to the activity. PT Semen Tonasa is a fabrication company doing business in the field of cement industry and produces two types of cement, cement or Portland cement type 1 can (OPC) and Portland cement (PPC) Pazzolan. The benefits that can be gained if the company implemented the system of Activity-Based Costing are: elimination is obtained more accurate information, among others, to improve the quality of decision making. In the ABC product only burdened costs of resources and activities that are used and does not burdened by the cost of the resources and activities. This method causes the cost per unit of a more stable and consistent with the purposes of the imposition of costs to the product result in activity.